Respuesta :

Answer:

-24

Step-by-step explanation:

f(x) = 3x^3 -12x^2

f(2) = 3 * (2)^3 - 12 (2)^2

      = 3 (8) - 12 (4)

      = 24 - 48

      = -24

Answer:

D. f(2)= -24

Step-by-step explanation:

To solve this problem, we want to find what f(x), or y is, when x is equal to 2.

f(x)=3x³-12x²

Therefore, we can substitute 2 in for every x.

x=2

f(2)=3(2³)-12(2²)

Evaluate the exponents first.

2³ is equal to 2*2*2, which equals 8.

2² is equal to 2*2, which equals 4.

f(2)=3(8)-12(4)

Multiply 3 and 8.

f(2)=24-12(4)

Multipy 12 and 4

f(2)=24-48

Subtract 48 from 24.

f(2)=-24

Therefore, the correct answer is D. f(2)= -24